Efficacy and Safety of Jueyin Granules for Patients with Mild-to-Moderate Psoriasis Vulgaris: Protocol for a Multicenter Randomized Placebo-Controlled Trial. (9th April 2020) - Li, Su; Zhang, Cang; Zhang, Hong-Ya; Zhou, Meng; Wang, Si-Nong; Xu, Rong; Zhou, Dong-Mei; Ji, Yun-Run; Lv, Jing-Jing; Yin, Qing-Feng; Wang, Rui-Ping; Li, Wei; et al.
Abstract : Introduction . The etiology and pathogenesis of psoriasis are complex. Blood-heat syndrome is the core pathogenesis of psoriasis. Based on theories of Chinese medicine (CM), heat-clearing and blood-cooling (HCBC) are the primary treatment. Very few studies have investigated the pharmacological mechanism of the CM HCBC method for treating psoriasis. This multicenter randomized controlled trial will focus on treating psoriasis blood-heat syndrome with the HCBC method using Jueyin granules (JYKL). This will be an objective and standardized evaluation of the efficacy, safety, and reproducibility of the HCBC method to obtain objective evidence meeting international standards that aim to establish a clinical standard suitable for the popular application of CM for treating psoriasis. Methods and Analysis . A five-center randomized double-blind placebo-controlled clinical design will be used in this study. At least 196 participants will be randomly assigned to receive either JYKL or placebo treatment approximately 30 minutes after meals in the morning and evening (one sachet per time, twice daily for 8 consecutive weeks). The study duration will be 17 weeks, including 1 week of screening, 8 weeks of intervention, and 8 weeks of follow-up. The patients will be evaluated every 2 weeks, and the measures will be compared with baseline values. The primary outcome measure will be the psoriasis lesion area severity index. We will also observe the recurrence rate, body surface area, physician global assessment, dermatology life quality index, quality of life index, visual analogue scale score, CM symptom score, combined drug use, and adverse events. This trial is registered with NCT03961230 .